Childhood maltreatment and NSSI in prisoners: mediation through self-identity and moderation by sensation-seeking - Li, Juan; Gu, Honglei; Xia, Tiansheng (Frontiers in Psychiatry, 2024)
The prevalence of non-suicidal self-injury (NSSI) among prisoners is widely recognized. However, most research conducted in prisons setting has focused on lifetime engagement in NSSI, with limited knowledge about its correlates and risk factors during imprisonment. Drawing on the integrated theoretical model of NSSI, this study aimed to examine the combined effects of childhood maltreatment (an environmental factor) and two intrapersonal factors, namely self-identity and sensation-seeking, on NSSI. 1042 Chinese male offenders participated in the current study, and regression analyses is used to examine the relationship among variables. The results revealed that self-identity mediated the association between childhood maltreatment and prisoners’ NSSI. Sensation-seeking moderated the relationship between self-identity and NSSI, and this connection was only significant for offenders with high sensation-seeking. We discuss the results of the current research and possible practical implications.